Supramolecular self-assembly of fluorescent peptide amphiphiles for accurate and reversible pH measurement. Issue 4 (10th January 2019) - Mei, Leixia; He, Suyun; Zhang, Li; Xu, Keming; Zhong, Wenying
Abstract : We report the synthesis and self-assembly of fluorescent peptide amphiphiles (NBD-PA) composed of a fluorescent NBD probe and a peptide derivative VVAADD with a C12 -alkyl-chain as the linker (NBD-C12 -VVAADD). Abstract : We report the synthesis and self-assembly of fluorescent peptide amphiphiles (NBD-PA) composed of a fluorescent NBD probe and a peptide derivative VVAADD with a C12 -alkyl-chain as the linker (NBD-C12 -VVAADD). The self-assembly of NBD-PA formed beta-sheet structures at neutral pH in aqueous solution, contributed to an ∼10-fold increase in the fluorescence and quantum yield of NBD molecules, and conferred a supramolecular hydrogel with excellent viscoelastic properties, while gel-to-sol transition of NBD-PA occurred rapidly when the pH value was adjusted to strongly alkaline ( e.g. pH 11). Through the pH-responsive self-assembly behavior, we further explored the relationship between fluorescence of NBD-PA and pH values. Interestingly, the fluorescence of the NBD-PA system exhibited an excellent sigmoidal function relationship ( R 2 = 0.9999) with the alkaline pH values, which enabled accurate pH measurement regardless of salt types and ionic strength of solvents. Furthermore, the fluorescence of NBD-PA was fully reversible upon cycles of pH shifts, with the chemical structure of NBD-PA well-maintained throughout the process. These features of NBD-PA would facilitate the design of in situ pH detection systems as well as pH-responsive actuators for various applications in future.